Development of data sharing and analysis software for un-wheeling repair of urban rail transit - ZANG Zhichao; DING Minghui; LI Ming (机车电传动)
The expansive operational network of urban rail transit presents increased demands and complexities for the operation and maintenance of vehicles. In order to improve the data sharing for un-wheeling repair of subway vehicles in networked operation settings towards a scientific and systematic system, alleviate the work intensity in the design process, and improve work efficiency, this paper presents the development of data sharing and analysis software for urban rail transit, based on various characteristic data involving the aspects such as vehicle base, vehicle operation, vehicle maintenance systems, and un-wheeling repair requirements, using the object-oriented Java programming language. This software is devised to automatically output reports, serving as a basis for auxiliary decision-making to aid related operational management authorities in urban rail transit planning, particular concerning networks and depots. Focusing on sharing un-wheeling repair data, the software is customizable to urban rail transit networks with varying scales and at different stages, and its output could provide a reference for the sustainable and high-quality development of urban rail transit.